Peran Corporate Social Responsibility Memoderasi Pengaruh Kinerja Lingkungan terhadap Kinerja Perusahaan - Hadiah Fitriyah; Rihlatus Saidah (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2022)
This study aims to determine the role of corporate social responsibility (CSR) in moderating the effect of environmental performance on company performance. The research population includes all Manufacturing Companies listed on the IDX for the 2017-2019 period. The sampling technique used is purposive sampling. The sample data taken are industrial consumer goods sector companies listed on the Indonesia Stock Exchange. The data analysis method used is partial least square (PLS) software. The results showed that environmental performance had an effect on company performance and corporate social responsibility was not able to moderate the influence of environmental performance on company performance. This is what provides an explanation that environmental performance is able to affect the company's performance as evidenced by the financial value with a higher rate of return and if the company does not have conflict issues regarding the environment, the company with EBBAs carries out its business operations, this proves that in the future environmental performance will provide influence on company performance.